High-sensitivity qualitative and quantitative analysis of human, bovine and goat milk glycosphingolipids using HILIC-MS/MS with internal standards. (15th July 2023) - Li, Zhenhua; Wang, Xiaoqin; Deng, Xiaoli; Song, Jiansen; Yang, Tong; Liao, Yujie; Gong, Guiping; Huang, Linjuan; Lu, Yu; Wang, Zhongfu
Abstract: Glycosphingolipids (GSLs) in human milk regulate the immune system, support intestinal maturation, and prevent gut pathogens. The structural complexity and low abundance of GSLs limits their systematic analysis. Here, we coupled the use of monosialoganglioside 1–2-amino-N-(2-aminoethyl) benzamide (GM1-AEAB) derivatives as internal standards with HILIC-MS/MS to qualitatively and quantitatively compare GSLs in human, bovine, and goat milk. One neutral glycosphingolipid (GB) and 33 gangliosides were found in human milk, of which 22 were newly detected and three were fucosylated. Five GB and 26 gangliosides were identified in bovine milk, of which 21 were newly discovered. Four GB and 33 gangliosides were detected in goat milk, 23 of them newly reported. GM1 was the main GSL in human milk; whereas disialoganglioside 3 (GD3) and monosialogangloside 3 (GM3) were dominant in bovine and goat milk, respectively; N -acetylneuraminic acid (Neu5Ac) was detected in >88 % of GSLs in bovine and goat milk. N -hydroxyacetylneuraminic acid (Neu5Gc)-modified GSLs were 3.5 times more abundant in goat than in bovine milk; whereas GSLs modified with both Neu5Ac and Neu5Gc were 3 times more abundant in bovine than in goat milk. Given the health benefits of different GSLs, these results will facilitate the development of custom-designed human milk-based infant formula. Graphical abstract: Unlabelled Image